Implementasi Edukasi Internet Sehat Berbasis Perkembangan IPTEK bagi Pelajar MA NWDI Mujahidin Pringgasela - Permana, Baiq Andriska Candra; Muhammad Wasil; Muhamad Sadali; Mahpuz; Zulkifli (Universitas Hamzanwadi, 2025)
Technological progress has undeniably made it easier for students to access information and complete their daily tasks. However, it has also introduced a set of emerging challenges, including the rapid spread of online gambling, misinformation, and a noticeable decline in digital manners among young users. Responding to these concerns, the Internet Sehat socialization program was initiated at MA NWDI Mujahidin Pringgasela. The program aimed to strengthen students’ understanding of safe, polite, and responsible internet use while emphasizing the serious legal consequences associated with online gambling. An educative–informative model was adopted because it aligns well with the characteristics of the students, the needs of the partner institution, and the nature of the material presented. This model integrates educational explanation with clear, direct, and contextually relevant information. Given that senior high school students are at a cognitive stage where they benefit most from concrete examples, real-life cases, and two-way interaction, this approach helps ensure that the material is easy to understand.. The results of the activity were highly encouraging. The satisfaction level among the 50 participating students reached 87.8%, with most responses falling into the “very satisfied” and “satisfied” categories. Observations during the session further indicated increased enthusiasm and improved comprehension regarding the dangers of online gambling and the importance of practicing safer and more ethical online behavior. Equally important, the program helped strengthen cooperation between the school, the university team, the police, and the village administration, reinforcing their shared commitment to protecting students from various digital threats.